New morphological data on fat bodies of semi-engorged females of Amblyomma cajennense (Acari : Ixodidae) - Denardi, Sandra Eloisi [UNESP]; Bechara, Gervasio Henrique [UNESP]; Camargo Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
The present ultramorphological, histological and ultrastructural study on the fat body of semi-engorged females of Amblyomma cajennense revealed that this tissue is diffuse and consists of strands of cells surrounding the tracheal trunks. Morphometric analysis showed that the cellular and nuclear areas of round-shaped trophocytes are larger than those of cuboidal trophocytes, indicating that the arrangement of the former provides more contact area with the haemolymph. In this species, the fat body is found right underneath the integument and around organs. It consists of two cell types that despite distinct morphological characteristics and locations in the tissue, present the same histological features. In this study, these cells were termed cuboidal trophocytes when arranged as strands of cells and present in larger numbers, and round-shaped trophocytes when lying on these strands and observed in fewer numbers. Histological observations revealed that both types of trophocytes have one nucleus in their cytoplasm and also exhibit numerous vacuoles of different sizes and contents. Ultrastructural examination revealed that the organelles more frequently observed were the vesicular and lamellar rough endoplasmic reticulum, and mitochondria with tubular crests, indicating that they might be involved in lipid synthesis. Smooth endoplasmic reticulum was not observed. Cuboidal trophocytes arranged in strands, despite being closely associated, do not exhibit fused plasma membranes. Rather, the fusion of basal lamina of two neighboring cells is occasionally observed, acting as a selective permeability barrier. Here, a new terminology for tick fat body is proposed. It is based on fat body location (parietal, when located right underneath the integument instead of peripheral; and perivisceral, when located around organs instead of central) terminologies previously suggest by Obenchain and Oliver and for the cells constituting them, cuboidal trophocytes when arranged as strands, and round-shaped trophocytes when lying on these strands. Nephrocytes were not observed in semi-engorged females of A. cajennense. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Amblyomma cajennense; Fat body; Ticks; cuboidal and round-shaped trophocyte; Ixodidae